Choice without consciousness: Women's participation in household decisions and gender equality in children's education - Sundus Saleemi; Chiara Kofol (University of Bonn, Center for Development Research (ZEF), 2020)
In this paper, we test if households where women participate in decisions regarding children's education and allocation of household education budgets incur more equal expenditures on education of boys and girls. Moreover, we test if women's awareness of gender equality can reduce inequality between boys and girls at the household level. We estimate these effects using three rounds of longitudinal data of rural households in Pakistan. We use both household and year fixed effects to control for endogeneity of the dependent and explanatory variables. The results suggest that households where women participate in decisions regarding children's education spend higher shares of education expenditures on education of girls in the secondary school age group (11-16). The results of Heckman Selection Model, corroborated by an estimated logit model, suggest that in households where women participate in children's education decisions and where women are aware of gender equality in education, girl children are more likely to be enrolled in school. The paper contributes to the refinement of measures of women's empowerment and to understanding of the mechanisms to achieve gender equality in education.
Keywords: D19; D63; J16; 330; empowerment; inequality; gender; household decision-making; intra-household resource allocation